Uma descrição da pesca artesanal, no período 2015-2017, no porto de Vila Nova e Vitória do Xingú, Pará, Brasil - LIMA, Vanessa do Nascimento (2022)
Artisanal fishing in Vila Nova is a traditional activity that involves commercial and subsistence exploitation of fishing resources by small vessels and the use of simple fishing techniques. Based on the collection of CPUE data by fishermen in the port of Vila Nova and a rocker at the port of Vitoria do Xingu, it was possible to verify that something has influenced the artisanal fish catch, leading to a significant decrease in the quantity of fish captured during 2015, and the later years.